2020
DOI: 10.1101/2020.06.12.20122374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal clinical and laboratory response to interleukin-6 receptor blockade with Tocilizumab in 89 hospitalized patients with COVID-19 pneumonia

Abstract: Background:. Emerging evidence links morbidity and mortality of pandemic COVID-19 pneumonia to an inflammatory cytokine storm. Methods: Eighty nine patients with COVID-19 pneumonia and heightened systemic inflammation (elevated serum C reactive protein and interleukin-6 levels) were treated with Tocilizumab (TCZ), a human monoclonal IgG1 antibody to the interleukin-6 receptor. Results: Clinical and laboratory improvement was seen comparing baseline and 1-2 day post-infusion indices. Among 72 patients not recei… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…All patients discharged on average 15.1 day after tocilizumab. By day 5 after TCZ, 75.0% of patients had lower oxygen intake Poor quality score (NOS) In case of fever within 12 h, single additional dose Pre-print not peer reviewed studies Fomina et al 37 Single-centre retrospective observational study (Russia) Hospitalized patients with COVID-19 (n = 89) Tocilizumab 400 mg No comparison Clinical course 63/72 not mechanically ventilated patients were discharged, 1/72 died, 8/72 remained in hospital; 10/17 mechanically ventilated patients died and 7/10 remain in hospital Poor quality score (NOS) Gorgolas et al 36 Single-centre retrospective observational study (Spain) Hospitalized patients with COVID-19 (n = 186) Tocilizumab single dose of 400−600 mg (16 received two doses and 1 received three doses) No comparison Intubation or death after 24 h from administration 51 patients were intubated or dead at day 15; 19 patients needed intubation (of whom 4 died) and 36 died (32 of whom were not intubated). 11 (5·9%) patients had serious adverse reactions, 13 cases (6·3%) of secondary acquired infections Poor quality score (NOS) Ip et al 31 Multicentre, retrospective, observational, study (USA) ICU patients with COVID-19 (n = 547) Tocilizumab: 400 mg (96%), followed by 800 mg (1%), 8 mg/kg (1%), 4 mg/kg (1%), and missing dosing (1%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients discharged on average 15.1 day after tocilizumab. By day 5 after TCZ, 75.0% of patients had lower oxygen intake Poor quality score (NOS) In case of fever within 12 h, single additional dose Pre-print not peer reviewed studies Fomina et al 37 Single-centre retrospective observational study (Russia) Hospitalized patients with COVID-19 (n = 89) Tocilizumab 400 mg No comparison Clinical course 63/72 not mechanically ventilated patients were discharged, 1/72 died, 8/72 remained in hospital; 10/17 mechanically ventilated patients died and 7/10 remain in hospital Poor quality score (NOS) Gorgolas et al 36 Single-centre retrospective observational study (Spain) Hospitalized patients with COVID-19 (n = 186) Tocilizumab single dose of 400−600 mg (16 received two doses and 1 received three doses) No comparison Intubation or death after 24 h from administration 51 patients were intubated or dead at day 15; 19 patients needed intubation (of whom 4 died) and 36 died (32 of whom were not intubated). 11 (5·9%) patients had serious adverse reactions, 13 cases (6·3%) of secondary acquired infections Poor quality score (NOS) Ip et al 31 Multicentre, retrospective, observational, study (USA) ICU patients with COVID-19 (n = 547) Tocilizumab: 400 mg (96%), followed by 800 mg (1%), 8 mg/kg (1%), 4 mg/kg (1%), and missing dosing (1%).…”
Section: Resultsmentioning
confidence: 99%
“…We retrieved 13 published clinical studies 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 and 15 pre-print (i.e. pre peer review) clinical studies, 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 respectively evaluating 1396 and 4380 patients, for a total of 5776 patients. The main characteristics of the included clinical studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In a Russian clinical study [ 75 ], 89 patients with COVID-19 received TCZ. Mechanical ventilation was provided for 17 (19%) of these patients; the remaining patients received supplemental oxygen.…”
Section: Efficacy Of Anti-il-6r and Anti-il-6 Monoclonal Antibodies Imentioning
confidence: 99%
“…There are currently 14 clinical trials on this drug all over the world the result of which is yet to be published ( Jones et al, 2010 ). Another study with 89 patients showed lower mortality and rapid improvement in CRP and lymphocyte counts in addition to clinical indices ( Formina et al, 2020 ).…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%